Consumption of Jelly Combination of Salacca Seed (Salacca zalacca) and Moringa Leaves Flour (Moringa oleifera) on Hemoglobin level in Female Adolescents with Moderate Anemia - Wijayanti, Poppy; Dewi, Yulia Lanti Retno; Indarto, Dono (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Adolescent girls are at risk for iron-deficiency anemia. Various food fortifications have been developed to reduce the incidence of anemia. This study aimed to investigate the effect of consumption of jelly combined with salacca pondoh seed flour and Moringa leaf flour on hemoglobin levels in adolescent girls with moderate anemia.Subjects and Method: The Randomized Control Trial study was conducted in high schools, Banyuwangi, East Java, from August to September 2020. A total of 75 high school girls with moderate anemia were randomly divided into three groups with 25 people in each group, namely: (1) Control group (C) get a combination of 100g plain jelly, and iron tablets; (2) Treatment group 1 (T1) received 100g of jelly combined with 14.9g of salacca pondoh seed flour and 5.7g of Moringa leaf flour; and (3) Treatment group 2 (T2) received 100g of jelly which had been combined with 7.5g of salacca pondoh seed flour and 3g of Moringa leaf flour. The treatment was given twice per week for 8 weeks. The dependent variable is hemoglobin level. The independent variable was administering a combination of jelly with salacca seed flour and Moringa leaf flour. Hemoglobin data was taken by laboratory examination on days 30 and 60. Data were analyzed using One Way Anova.Results: After the intervention, the average hemoglobin levels in the three groups increased during the 30th day of observation: C (Mean= 14.68; SD= 0.75), T1 (Mean= 15.50; SD= 0.90), and T2 (Mean= 14.47; SD= 0.79). There was an average increase in hemoglobin levels in the three groups during the 60th day of observation, namely: C (Mean= 14.96; SD= 0.81), T1 (Mean= 15.20; SD= 0.78), and T2 (Mean= 14.96; SD= 0.69). On the 30th and 60th day observations, the difference in mean between the three groups was not statistically significant (p= 0.412) and (p= 0.703).Conclusion: The administration of jelly combined with salacca pondoh seed flour and Moringa leaves is effective compared to plain jelly with iron tablets in increasing Hb levels.Keywords: combination jelly, salacca seeds, moringa leaves, hemoglobin, anemia, young womenCorrespondence: Poppy Wijayanti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: popzala04@gmail.com. Mobile: +6285235925411.Indonesian Journal of Medicine (2021), 06(03): 307-314https://doi.org/10.26911/theijmed.2021.06.03.08